Inequity in infant mortality and pediatric services in Bogotá: a new model of analysis for Latin America (2018)
Objective To describe the correlation between the availability of health services and infant mortality in Bogotá. Materials and Methods This study involved data on infant mortality rates (IMR), ratio of pediatric hospital beds (RPHB) and emergency service centers by locality (ESC) for the years 2010-2016. A GINI coefficient and a Pearson correlation coefficient (r) were estimated. Results During the period 2010-2016, there were 726 946 live births (LB) and 7 681 children under 1 year died. Insurance coverage was 94.7%, with 75% of the children affiliated in the private scheme. The infant mortality rate decreased until reaching 9.11 in 2016, but an increase was observed in the localities of Tunjuelito, Antonio Nariño and Ciudad Bolivar with >12 per 1 000 LB. Conclusions Health services have an inequitable distribution with a GINI of 0.44 for ESC and 0.701 for RPHB. There was a correlation with infant mortality in localities with the lowest ESC r (-0.340) and RPHB r (-0.648) in 2016. © 2018, Universidad Nacional de Colombia. All rights reserved.